Rhetoric Of The Master Of Ceremony (Communication Style In Guiding Kaili Tribe Wedding Events In Central Sulawesi) - Sumarni Zainuddin; Donal Adrian; Muhammad Wahid; Moch Rezky Ramadhan; Magfirah Atsari Ayu Fadli; Romaulina Tampubolon (Jurnal Mamangan, 2024)
The Master of Ceremony (MC) is perpetrator frequent communication face to face direct with audience There are many people who have a certain style in conveying messages when leading wedding ceremonies for the Kaili tribe in Central Sulawesi. Objective study that is know And give description related with Master of Ceremony's communication style in guiding sacred wedding events based on the customary patterns of the Kaili Tribe in Central Sulawesi   Method study qualitative with technique taking informant use purposive. Technique collection data is interview deep ( Indepth Interviewing) And observation direct For technique analysis use Data Reduction, Presentation Data And Conclusion Drawing / Verification The research results show that in the marriage ceremony procession, the MC guides the event precisely and accurately or what is called (precive), that is, there is no need to add too much vocabulary, because there will be a session for traditional parents and religious figures to speak. Furthermore, at the Kaili traditional wedding reception there was also limited inclusion, namely only the Peulu Cinde dance as a dance of appreciation for the bride and groom who were present and the invited guests. The MC also plays a role in explaining the meaning of the dance to support the course of the event or what is called (relaxed). At the Kaili tribe's wedding reception, an MC must be able to play a tone of voice (dramatic), use good body gestures (animated expressive), be able to argue logically according to the event's friends (argumentative), show polite etiquette in conveying good messages. speak Kaili and Indonesian. This will also be related to the behavior shown (friendly), because good ethics can give a positive impression to anyone (impression leaving).